PENGEMBANGAN MODUL PANDUAN “PERENCANAAN DAN ANALISIS SISTEM DRAINASE DIGITAL BERBASIS BIM: AUTODESK CIVIL 3D DAN STORM AND SANITARY ANALYSIS (SSA)” - Lenadya, Adelya Sefira; Wulandari , Fadila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is driven by the limited availability of Indonesian-language teaching materials and practical references that support the improvement of drainage system planning, analysis, and learning based on Building Information Modeling (BIM). The objective of this study is to develop a comprehensive guidebook for the Modeling and Evaluation of Drainage Systems using Autodesk Civil 3D – Storm and Sanitary Analysis (SSA) within a BIM framework. This study follows a Research and Development (R&D) approach, utilizing the 3D model (Define, Design, Development). Conducted at the State University of Malang, the research involved two subject matter experts and two media experts as evaluators. The research instrument consisted of a validation questionnaire used by these experts to assess the feasibility and quality of the guidebook. The results indicate that the developed product meets quality standards and is categorized as "Feasible." Evaluations from subject matter experts yielded an overall average score of 96.5%, while implementation trials resulted in a score of 93.3%. Consequently, this guidebook is declared suitable for use as a reference for civil engineering students and practitioners in BIM-based drainage system planning and evaluation.